THE IMPLEMENTATION OF THE NATIONAL DIGITAL SAMSAT (SIGNAL) PROGRAM IN POLDA METRO JAYA JURISDICTION FROM A SYSTEMIC PERSPECTIVE - Arie Andhika Silamukti; Vita Mayastinasari; Ezra Aminanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
The focus of this study is to examine the significance of implementing the National Digital Samsat (SIGNAL) program in the Metro Jaya Police Jurisdiction, as well as the factors that impede and support the program's execution, and to analyze outcome practices from a systemic perspective in the process of implementing the National Digital Samsat (SIGNAL) in the Metro Jaya Police Jurisdiction. In this study, the type of data collected suggests that the research approach used was qualitative. This writing of this study uses a descriptive method. This study was performed in the Samsat office in the Polda Metro Jaya, precisely in the Special Capital Area of Jakarta. According to the findings, the digital service of the Polda Metro Jaya SIGNAL program has been functioning as expected. In addition, a number of components, including equipment (computers, etc.), vehicles, and human resources, are capable of supporting the operation of the digital service program SIGNAL Polda Metro Jaya. In addition, the implementation of the SIGNAL service program is hindered by a number of obstacles, including a network issue that prevents the service from being handled out as it must be linked to the network in order to perform services (such as determining the total amount of Motor Vehicle Tax payments), an ineffective communication when carrying out duties, and the ongoing use of broker services by individuals who do not wish to deal with Motor Vehicle Tax payments. The involvement of brokers holds back the creation of clean services that adhere to the regulatory requirements.